Paracentrické inverze lidských chromozómů a jejich rizika - Balícek, P (Casopis lekaru ceskych, 2004)
The incidence of paracentric inversions in the general population has not been clearly established, it ranges from 0.09 to 0.49/1,000. Homologue pairing during melosis in a paracentric-inversion heterozygote is maximized by the formation of an inversion loop. If a crossing-over occurs within this loop, dicentric and acentric chromosomes are formed. Resulting gametes can have variety of duplications and deficiencies and give a non-viable progeny. One of the exceptions to the rule is a mutation event "U loop recombination". From U-loop event a monocentric recombinant chromosome can arise by an abnormal process, which involves chromatid breakage and reunion. Most of the paracentric inversions in man are harmless and the risk of heterozygotes having a child with an unbalanced karyotype is relatively low. In carriers of an accidentally discovered paracentric inversion, amniocentesis is optional. However, in some cases, it is difficult to distinguish between a paracentric inversion and paracentric insertion--the risk of the insertion is about 15%. When a de novo inversion is detected in amniotic fluid, the overall risk for two-break rearrangements is 6.7%.
Keywords: Karyotyping; lidé; Recombination, Genetic; Chromosome Inversion; gametogeneze; rekombinace genetická; karyotypizace; chromozomální inverze; Gametogenesis; Humans